A review of the MIS 5e highstand deposits from Santa Maria Island (Azores, NE Atlantic): palaeobiodiversity, palaeoecology and palaeobiogeography. (15th April 2015) - Ávila, Sérgio P.; Melo, Carlos; Silva, Luís; Ramalho, Ricardo S.; Quartau, Rui; Hipólito, Ana; Cordeiro, Ricardo; Rebelo, Ana Cristina; Madeira, Patrícia; Rovere, Alessio; Hearty, Paul J.; Henriques, Diamantino; et al.
Abstract: The privileged location of Santa Maria Island (Azores archipelago) in the middle of the North Atlantic makes the fossiliferous outcrops on this island of utmost importance to gain a better understanding of how coeval living communities relate to the broader evolutionary and biogeographic history of the Atlantic basin during the late Neogene and the Quaternary. Here we focus on this island's MIS 5e fossil record, offering a comprehensive review on the palaeobiodiversity, palaeoecology and palaeobiogeography of the biota living in the mid North Atlantic during this interglacial. Several studies in oceanic islands stress the huge impact of sea level changes on insular communities. Pleistocene sea-level changes occur during the short-time events known as "Terminations" (associated to glacial/interglacial shifts) as well as with the onset of glaciations (associated to interglacial/glacial shifts). Both are responsible for extinctions and local disappearance of species, bottleneck effects and formation of new species, resulting in community structure changes. This work increases the number of fossil marine taxa reported from the Last Interglacial deposits of Santa Maria to 143 species. All the 19 new records are molluscs (13 gastropods and 6 bivalves), thus increasing the number of fossil molluscs to 136 species. Although thermophilic members of the "Senegalese" tropical fauna were found in these deposits, many of the most emblematic species (e.g., Persististrombus latus (= Strombus bubonius ), Cymbula safiana, Harpa doris, Cardita senegalensis, Barbatia plicata, Ctena eburnea or Hyotissa hyotis ) are absent, suggesting that they did not reach the Azores. Our results indicate that the main differences between the species composition of the MIS 5e and the present-day shallow-water Azorean communities are probably due to the dropping of sea surface temperature associated with the onset of the last glaciation, which had both direct and indirect effects on species ecology. A group of 21 thermophilic species was directly affected by the lower sea surface temperature, whereas a group of four sand-associated species was indirectly but similarly affected by the lowering of the sea level. Both groups have locally disappeared from the Azores. However, none of the extant endemic species found on the studied MIS 5e outcrops was apparently affected by the lowering SST. In contrast to the biogeographical relationships of the recent Azorean shallow marine molluscs, which are predominantly with the Mediterranean Region, Portugal and with the Madeira and Canary Islands archipelagos, the palaeobiogeographical relationships of the MIS 5e Azorean marine molluscs are mainly with Canaries and West Africa. Despite the general low similarity of the biogeographical relationships between the Azores and Cape Verde Archipelago, on both the recent and the MIS 5e analysis, this similarity is nevertheless higher for the MIS 5e mollusc assemblages, emphasizing the role of Cape Verde as an important source of warm-water species during the Last Interglacial. Highlights: An updated checklist of the MIS 5e molluscs of the Azores is provided. MIS 5e palaeobiogeographical relationships of the Azores fauna different from the present. Most of the "Senegalese" tropical fauna did not reach the Azores during MIS 5e. None of the extant Azorean endemic species found on the MIS 5e outcrops was affected by the lowering SST. Cape Verde was an important source of warm-water species during MIS 5e.